Detection of Human Paragonimiasis by ELISA Using Recombinant Paragonimus westermani Cysteine Protease 7 - Andrade-Gomes, Luana Gabriele (2023)
Paragonimiasis is an important but neglected foodborne trematodiasis caused by Paragonimus mexicanus in Costa Rica. Immunological techniques for diagnosing this parasitosis in humans do not exist in Central America. The objective of the present study was to use recombinant Paragonimus westermani cysteine protease 7 to standardize an ELISA for the detection of antibodies against Paragonimus spp. Human sera positive for P. westermani, P. mexicanus, or Paragonimus spp., human sera infected with other helminths, as well as sera of healthy humans without parasitic infections, were analyzed. The sensitivity of the ELISA was 92.9%, and the specificity was 91.9%. This report is the first to describe the development of an ELISA for the diagnosis of Paragonimus spp. in Costa Rica and Central America. Using this ELISA in the health system of Costa Rica is recommended to detect infections.